Continued benefit demonstrated with BAY 81-8973 prophylaxis in previously treated children with severe haemophilia A: Interim analysis from the LEOPOLD Kids extension study. Issue 189 (May 2020) - Kenet, Gili; Ljung, Rolf; Rusen, Luminita; Kerlin, Bryce A.; Blanchette, Victor; Saulytė Trakymienė, Sonata; Uscatescu, Valentina; Beckmann, Horst; Tseneklidou-Stoeter, Despina; Church, Nikki
Abstract: Introduction: BAY 81-8973 (Kovaltry®), a recombinant factor VIII (rFVIII) product, was efficacious and well tolerated in paediatric previously treated patients (PTPs) with severe haemophilia A for ≥50 exposure days (EDs) in the LEOPOLD Kids study. Because long-term prophylaxis (≥100 EDs) can provide substantial patient benefits, FVIII products should demonstrate long-term safety and efficacy. Aim: To demonstrate long-term (≥100 EDs) efficacy and safety of BAY 81-8973 in paediatric PTPs. Methods: PTPs aged ≤12 years with severe haemophilia A without inhibitors could continue in the ongoing open-label extension study after completing ≥50 EDs in the LEOPOLD Kids main study. Patients received BAY 81-8973 for prophylaxis (25–50 IU/kg ≥2×/week), bleed treatment, and surgery. Bleeds were documented in electronic patient diaries. Inhibitor development was monitored every 6 months. Results: At the August 2017 interim data cutoff, 46 patients (median [range] age at enrolment, 6.0 [1.0–11.0] years) had spent a median (range) of 602.5 (148–1069) EDs and 4.6 (1.0–5.9) years in the main plus extension studies. Median (quartile [Q]1; Q3) annualised bleeding rate for bleeds within 48 h after a prophylaxis infusion and total bleeds was 1.0 (0.2; 1.9) and 2.0 (0.4; 3.6), respectively. Most (>94%) bleeds were mild or moderate; 71.8% were treated with ≤1 infusion. BAY 81-8973 was also well tolerated with only one treatment-related adverse event (transient, low-titre inhibitor which did not require treatment adjustment). Conclusion: BAY 81-8973 was efficacious for prophylaxis and treatment of bleeds during >4.5 years in paediatric PTPs with severe haemophilia A. Highlights: In haemophilia, prophylactic FVIII replacement is the standard of care Char = 77 BAY 81-8973 is an unmodified, full-length recombinant human factor VIII Char = 71 The LEOPOLD Kids extension has shown excellent outcomes in paediatric patients Char = 83 BAY 81-8973 was efficacious and well tolerated for >4.5 years for prevention and treatment of bleeds Char = 85